The Correction of Fiber Throughput Variation due to Focal Ratio Degradation. Issue Volume 9:Issue S298(2013) (6th January 2014) - Chen, Jianjun; Bai, Zhongrui; Li, Guangwei; Zhang, Haotong
Abstract: The focal ratio degradation (FRD) of optical fibers is a major source causing light loss to astronomical multi-fibre instruments like LAMOST (Oliveira, A. C, et al . 2005). The effects of stress and twist during mounting and rotation of the fibers could change the FRD for individual fibers (Clayton 1989), which means that the transmission efficiency of each individual fiber will vary. We investigate such throughput variation among LAMOST fibers and its relevance to the intensity of sky emission lines (Garstang 1989) over the full wavelength coverage. On the basis of the work, we present an approach to correct the varied fiber throughput by measuring the strength of the sky emission lines as the secondary throughput correction.